Percutaneous transhepatic biliary tract embolization using gelatin sponge. (October 2019) - Augustin, Anne Marie; Cao, Victoria; Fluck, Friederika; Kunz, Julian; Bley, Thorsten; Kickuth, Ralph
Background: Percutaneous biliary drainage (PTBD) is a necessary procedure in several benign and malignant conditions. After PTBD removal biliocutaneous fistula is a rare but potential complication. Different embolization agents have been used for transhepatic catheter tract embolization in the past, while there is only little experience using gelatin sponge for this procedure. Purpose: To evaluate the feasibility and safety of PTBD tract embolization with gelatin sponge. Material and Methods: Between July 2008 and August 2017, 98 patients have been treated with PTBD access embolization using gelatin sponge. PTBD was performed in patients with malignant (67%) or benign (33%) bile duct obstruction. Outcome measures included technical success (complete cessation of bile flow out of the percutaneous access tract), clinical success (intermediate and long-term absence of biliocutaneous fistula, absence of right upper quadrant pain as typical symptom for bile leakage into the peritoneal cavity and absence of hemorrhage out of the catheter tract during follow-up inspections), and the rate of major and minor complications. Results: Technical success with effective control of bile flow out of the percutaneous access tract was achieved in 97/98 patients (99.0%). Clinical success attributed to gelatin sponge embolization was documented in 96/98 procedures (98.0%). In one case, slight bleeding out of the percutaneous drainage tract occurred after drainage removal and embolization of the access tract. Bleeding was self-limiting; no blood transfusion or surgical intervention was necessary. Conclusion: PTBD tract embolization with gelatin sponge is a feasible and safe method with a low rate of therapeutically relevant complications.